An Objective Measurement of Nasality - Murthy, Sarguna (Journal of All India Institute of Speech and Hearing)
The nasal resonance is a highly distinctive readily perceived acoustic quality which may occur with orally produced sounds to invoke specific phonetic contrasts. The penetrating quality of nasality as an acoustic property is unacceptable to listeners when it is injected dominantly and nonphonetically into speech.